2017
DOI: 10.1016/j.biocon.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

After the epidemic: Ongoing declines, stabilizations and recoveries in amphibians afflicted by chytridiomycosis

Abstract: The impacts of pathogen emergence in naïve hosts can be catastrophic, and pathogen spread now ranks as a major threat to biodiversity. However, pathogen impacts can persist for decades after epidemics and produce variable host outcomes. Chytridiomycosis in amphibians (caused by the fungal pathogen Batrachochytrium dendrobatidis, Bd) is an exemplar, with impacts ranging from rapid population crashes and extinctions, to population declines and subsequent recoveries. Here, we investigate long-term impacts associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 87 publications
2
102
1
Order By: Relevance
“…Our results also indicate that suitability for Bd decreases with elevation, which is opposite to what other authors have found regarding the best conditions for Bd growth (Woodhams and Alford , Scheele et al. ). Nevertheless, the high altitude areas where suitability is indeed very low (Andes mountains in blue in Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results also indicate that suitability for Bd decreases with elevation, which is opposite to what other authors have found regarding the best conditions for Bd growth (Woodhams and Alford , Scheele et al. ). Nevertheless, the high altitude areas where suitability is indeed very low (Andes mountains in blue in Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…Both species are threatened, and the Southern Corroboree Frog is critically endangered. For 40 years, Southern Corroboree Frogs have experienced a catastrophic population decline due, primarily, to living in sympatry with a chytridiomycosis reservoir species ( Crinia signifera ; Hunter, Marantelli, et al, ; Hunter, Speare, et al, ; Scheele et al, ). Southern Corroboree Frogs are now functionally extinct (Brannelly, Roberts, Skerratt, & Berger, ).…”
Section: Introductionmentioning
confidence: 99%
“…, Scheele et al. ). Hotter temperatures are less optimal for chytrid: temperatures above 26°C significantly slow growth, with a lethal thermal maximum at 28–29°C for Queensland‐derived chytrid (Stevenson et al.…”
Section: Methodsmentioning
confidence: 98%
“…, Scheele et al. ), and it is likely that in the future they will continue to recolonize up the elevation gradient. However, we could not build this into the models due to a lack of data on the rate or potential ultimate extent of this recolonization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation